Antinociceptive, anti-inflammatory, and anti-dysmenorrheal activities of aerial parts of Cannabis sativa L. from the sub-middle region of the Vale do São Francisco - Menezes, Pedro Modesto Nascimento; Rocha, João Lázaro de Oliveira; Silva, Murilo Soares; Silva, Juliane Maria dos Santos; Araújo, Tarcísio Cícero de Lima; Deus, Deborah Lays Silva; Rolim-Neto, Pedro Jose; Matos, Luana Fernandes; Massaranduba, Ana Beatriz Rodrigues; Silva, Fabrício Souza; Rolim, Larissa Araújo (Frontiers in Pharmacology, 2025)
IntroductionCannabis sativa L. has been used for thousands of years to treat intestinal and uterine diseases and as an anti-inflammatory, analgesic, and antiepileptic, among others. This study aimed to conduct preclinical studies based on the ethnopharmacological properties of C. sativa.MethodsFor this purpose, the police and health authorities provided the raw plant material, and a crude ethanolic extract of the aerial parts of C. sativa (APCs) was produced, which was subsequently chemically analyzed using combined chromatographic and spectrometric methods. Subsequently, APCs were administered to Swiss mice and Wistar rats for evaluation using the open field test, acetic acid-induced abdominal contraction model, hot plate test, formalin test, carrageenan-induced paw edema, Saccharomyces cerevisiae-induced fever, and primary dysmenorrhea models.ResultsChemical analysis suggests the presence of classic cannabinoids, such as cannabidiol, tetrahydrocannabinol, and cannabigerol, as well as flavonoids and alkaloids. The doses used in the open field test were 1, 3, 10, 30, and 100 mg/kg (gavage, po), with the last two doses responsible for reducing mobility and inducing hypothermia in the animals. In subsequent pharmacological protocols, the doses used were 1, 3, and 10 mg/kg (gavage, po). In the abdominal contraction model, the number of writhing events was reduced by APCs at a dose of 10 mg/kg [median 0.5 (Q25 = 0; Q75 = 5.75, p < 0.05)]. In the hot plate test, the doses of 1, 3, and 10 mg/kg increased the latency time to 17.67 ± 1.33, 18.50 ± 1.31, and 17.33 ± 1.69 s (p < 0.05), respectively. In the formalin test, the effect was restricted to the first phase, with values of 42.33 ± 7.588, 45.50 ± 6.657, and 39.50 ± 7.869 s (p < 0.05) in paw-licking time. In paw edema, the doses of 1 and 3 mg/kg were more constant, restricting the volume to 0.168 ± 0.004 and 0.150 ± 0.004 mL (p < 0.05), respectively. In dysmenorrhea, the doses of 3 and 10 mg/kg reduced abdominal contractions [0 (Q25 = 0; Q75 = 3.0) and 1.0 (Q25 = 0; Q75 = 3.0)].ConclusionAPCs at the tested doses did not promote an antipyretic effect. These data indicate that APCs have antinociceptive, anti-inflammatory, and anti-dysmenorrheal effects in animal models.